Implementation of walk-through audits for designing energy management system: A first step towards an efficient campus. Issue 1 (April 2020) - Yandri, E; Ariati, R; Uyun, A S; Setyobudi, R H; Anne, O; Susanto, H; Vincevica-Gaile, Z
Abstract: The purpose of this study is to design a concept of energy management control system (EMCS) at the UNSADA campus, Jakarta, Indonesia by utilizing the results of the previous walkthrough audit. EMCS is an important first step by involving all parties on campus to be concerned the sustainable energy savings. The energy efficiency program utilizes the campus as an energy laboratory to identify, recommend, implement and evaluate the energy consumption, so that the expected energy efficiency targeted by the top managements can be achieved. This program is motivated by several reasons, such as; to support government policies in reducing dependence on fossil energy by implementing energy conservation programs; as a reflection of compliance with the implementation of educational service buildings (including the campus in Jakarta); a vision as the efficient campus in energy consumption that has been determined by the campus management. To achieve these goals, there are four stages to be done; the preparation, the conducting audit, the audit analysis, and the recommendation for implementation. The results provide an overview of the opportunities to save the energy consumption and to develop EMCS by involving all stack-holders on campus.